Towards a brand-free philosophy: integrating Muji's design characters into Chinese packaging - Shahbudin, Shahrul Azman; Alli, Hassan; Wang, Hang; R.A. Effendi, Raja Ahmad Azmeer (Human Resource Management Academic Research Society, 2023)
This comprehensive review, titled "Towards a Brand-free Philosophy: Integrating MUJI's Design Characters into Chinese Packaging," delves into the unique design philosophy of MUJI, a Japanese retail company known for its brand-less, minimalist aesthetic, and explores the potential for integrating these principles into contemporary Chinese packaging design. Initially, the paper outlines MUJI’s historical context and the underlying principles that shape its design strategy, characterized by simplicity, functionality, and a subdued aesthetic that defies the clamor typically associated with branding. This study subsequently contrasts this approach with the current state of packaging design in China, which is marked by a rich history of artistry yet is facing challenges in the modern consumer landscape. Through case studies and theoretical analysis, this paper investigates the avenues and challenges associated with transplanting MUJI’s design characters into China’s packaging sector. It demonstrates that the integration of MUJI’s minimalist, brand-free philosophy can address current issues in Chinese packaging, such as overemphasis on opulence and visual complexity, offering a sustainable and culturally resonant alternative. The review concludes by forecasting potential trends of this integration and offering actionable recommendations for China's packaging industry to evolve towards a more harmonious, user-centered, and ecologically sustainable paradigm.